Optimizing the role of the Cahaya Ilmu library in Selomirah Village, Ngablak, Magelang Regency - Nur Hidayah; Muhammad Farhan Da’arul Fikri; Fira Sofana Tuzzahrok; Erra Erfieana; Siwi Luthfi Sandriya; Dzakiyya Silkha Uyun (Community Empowerment, 2022)
Social inclusion library is a National Library program that aims to improve the quality of human resources through literacy. This community service program aims to create a social inclusion library. The method used in this community service program goes through four stages, namely: observation, socialization, training, and mentoring. This community service activity received a positive response and was able to improve the knowledge and skills of librarians in realizing social inclusion-based libraries through various literacy improvement programs for the community.